The Impacts of Work-Family Conflict on Burnout among Female Lecturers - Zulkarnain, Zulkarnain; Yusuf, Elvi Andriana; Pulungan, Annisa Vanya (Makara Human Behavior Studies in Asia, 2015)
Indonesian females lecture are expected to perform double roles to do domestic chores and take care of their children. This condition may create conflicts if female lecturers cannot perform their duties as expected by their employers and families. These conflicts then turn into mental pressure and experiences of burnout. The aim of this study is to find out the impacts of family-work conflicts and burnout among female lecturers. The subjects of this study are 160 lecturers who are female, are married, and have children. Research data are generated using family-work conflict scale and burnout scale. The data are analyzed using regression analysis technique. The results of data analysis also show that the conflict between work and family strongly associate with burnout among female lecturers. The result findings also show that there are two dimensions of family-work conflicts which may cause burnout: behavior-based conflict dan time-based conflict. By implication, this study can help expand the understanding of burnout among female lecturers which may lead to the improvement of the quality of their working environments. In this way, better understanding of the impacts of living environments and individual characteristics on burnnouts can benefit the lecturers themselves and the institutions they work at.